Numerical investigation of oil-water separation on a mesh-type filter - Kim, Dae Kyung; Geunhyeok Choi; Ko, Tae-Jun; Shin, Seungwon; Kim, Seong Jin (Springer Verlag, 2022)
The oil-water separation plays a vital role in many engineering applications and environmental issues, which can be achieved using an oleophobic mesh that restricts the oil spreading along the mesh surface. However, unfortunately, the oil-water flow within a mesh hole could not be experimentally investigated due to the technical difficulty of observing the motion of the oil-water interface inside the mesh hole. In the present work, we use direct numerical simulation based on the level contour reconstruction method to investigate the two-phase oil-water flow through a mesh hole. Numerical solutions on two distinctive oleophilic and oleophobic surfaces are representatively compared in detail to elucidate the role of oleophobicity in oil-water separation under different external pressure gradients. Our numerical solutions indicate that the oil inertia through the mesh hole can pose a severe threat to the oil-water separation performance by forcing the contact line to spread even on a highly oleophobic surface. This inertial effect is found to be minimised by narrowing the mesh hole size. According to the numerical solutions, the narrowed hole improves not only the interfacial resistance but also the viscous dissipation that contributes to the resistance to oil penetration by dissipating the oil inertia. The effect of viscous dissipation is then discussed in terms of the regime map of oil penetration depth for various oleophobicities and external pressure gradients for two different hole sizes.